IMPACT OF NGO INITIATIVES ON EMPOWERMENT OF RURAL WOMEN - Matharu, Sukhjeet Kaur; Haryani, Sharda; Motwani, Bharti ,; Sharma, Prateek (International Journal of Psychosocial Rehabilitation, 2020)
India is an agrarian economy. Majority of Indians lives in the rural areas. A number of challenges in the area of health, education and employment are an obstacle to women development in rural areas. Numerous programmes have been initiated by Indian Government and for the development of women in rural areas. Apart from Government various non-governmental organizations, local self-governance institutions and Self-help groups bear a significant role in women empowerment in rural areas which is instrumental to their development. An empowered woman is key to the well being of their entire family as well to the entire community. The present study aims at analyzing the impact of NGO initiatives on empowerment of women. Primary data was collected from 310 women beneficiaries of NGOs working for the cause of rural women in and around Indore district of Madhya Pradesh in Central India with the help of a self designed questionnaire. The study identified a positive impact of NGO initiatives on the empowerment of rural women. Thus we can conclude that NGOs in India are effectively working towards upliftment of socio-economic status of the poor women in the rural areas thereby attaining the goal of rural management.